2020
DOI: 10.1596/978-1-4648-1568-3
|View full text |Cite
|
Sign up to set email alerts
|

Africa's Pulse, No. 21, Spring 2020 : An Analysis of Issues Shaping Africa’s Economic Future

Abstract: This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of The World Bank concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 27 publications
1
28
1
Order By: Relevance
“…COVID-19 movement restrictions limits social interactions and closure of certain sectors of the economy where farmers could get financial aid. Since the majority of SSA countries are dependent on agriculture, there is a high probability that the region may be threatened by the first serious recession in the region in 25 years, as the economic growth in the region will decline from 2.4% in 2019 to −2.1 to −5.1% in 2020 50 . It has been reported that many households in SSA, especially in rural communities, may be directly impacted by the predicted decline in economic growth, as the supply-side economic shocks such as those caused by the COVID-19 pandemic 51 .…”
Section: Environmental and Pest Challenges Overlapped The Movement Rementioning
confidence: 99%
“…COVID-19 movement restrictions limits social interactions and closure of certain sectors of the economy where farmers could get financial aid. Since the majority of SSA countries are dependent on agriculture, there is a high probability that the region may be threatened by the first serious recession in the region in 25 years, as the economic growth in the region will decline from 2.4% in 2019 to −2.1 to −5.1% in 2020 50 . It has been reported that many households in SSA, especially in rural communities, may be directly impacted by the predicted decline in economic growth, as the supply-side economic shocks such as those caused by the COVID-19 pandemic 51 .…”
Section: Environmental and Pest Challenges Overlapped The Movement Rementioning
confidence: 99%
“…Responses to address gaps in health and safety will affect both enterprises and workers in the informal sector, directly, but also indirectly, as ill-health or poor sanitation could result in economic losses from closures, absenteeism, as well as affecting consumer demand in the marketplace. Individuals in Africa have relatively high out-of-pocket expenses (Calderon et al 2020). Total health expenditure per capita in stood at US$32 in 2019, which is less than half the levels recommended by the World Health Organization (WHO) for low-income countries (US$86).…”
Section: Well-beingmentioning
confidence: 99%
“…A recent World Bank report (Calderon et al 2020) suggests that the vulnerability of informal firms to the demand effects can be assessed by estimating the share of businesses that are more affected. The share of jobs that can be done from home in Commonwealth African countries ( Figure 3) ranges from 18 to 25 per cent (Dingel and Neiman 2020), close to the world average, suggesting that some African economies may be able to continue to work during periods of stringent social distancing.…”
Section: The Unfolding Effects Of Covid-19 For Msmesmentioning
confidence: 99%
“…In fact, the COVID-19 crisis is expected to heavily affect African countries while the latter do not have enough fiscal space to launch major economic stimulus programs. Countries depending on mining and oil exports are expected to experience huge falls in growth that could be below 7 percentage points for oil-exporting countries, and below 8 percentage points for metal-exporting countries (Calderon et al, 2020). The potential losses in already low tax revenues due to the disruption of economic activities, the collapse in commodity revenues, and the increase in public health spending are expected to weaken fiscal positions in several Franc zone countries; resulting thus in limited room to fund economic stimulus plans (AU, 2020; World Bank, 2020a; World Bank, 2020b).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%